2020
DOI: 10.1109/tits.2019.2931797
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Car-Following Behavior in Terms of Safety Indicators Between China and Sweden

Abstract: Understanding car-following behaviour in different countries is essential for the design and development of autonomous driving and further development of active safety systems that can function well worldwide, in particular in mixed traffic conditions. However, very few studies exist that compare car-following behaviours in different countries based on real driving data. This paper analyses the similarities and differences of drivers' car-following behaviour, in terms of time gap, gap distance, and time to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…As previous studies shown, the driver's choices (to let the pedestrians cross the streets, overtake the bicycle, sound the horn, etc.) and the driving style change according to the country [30], [31], the topology of the road [32], [33], the type, the condition as well as the perception of the driver [34], [35]. Through our definitions, the ego-object can be implemented taking into account not only its characteristics (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies shown, the driver's choices (to let the pedestrians cross the streets, overtake the bicycle, sound the horn, etc.) and the driving style change according to the country [30], [31], the topology of the road [32], [33], the type, the condition as well as the perception of the driver [34], [35]. Through our definitions, the ego-object can be implemented taking into account not only its characteristics (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…e test route consisted of diverse driving scenarios such as urban roads and highways, as shown in Figure 3. e other details of the field tests are described in [39,40].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we assumed that the limited set of participants who took part in our experiment was representative of the driving population. This may not be the case as driver behavior can greatly vary between different regions and individuals [52], especially when taking exposure to cyclistovertaking maneuvers into account [6]. To better understand how well our model can represent driver behavior close to the boundary of their comfort zone, data from more critical maneuvers are needed.…”
Section: Limitationsmentioning
confidence: 99%